Meningkatkan Kepuasan Tamu Melalui Kualitas Pelayanan, Servicescape, dan Customer Experience di The Manggar Guesthouse - Dwi Rahmadianti, Ni Made; Istri Agung Maheswari, Anak Agung; Nurmalasari, Made Ratih; Lasmi, Ni Wayan (Masyarakat Ekonomi Syariah Bogor, 2025)
Tourism is a primary sector supporting Bali's economy, as it is capable of driving economic growth, creating job opportunities, and accelerating the development of tourist areas. Canggu is one of the regions experiencing an increase in guesthouse-based accommodation development, in line with the rising interest of tourists. However, The Manggar Guesthouse is facing a decline in occupancy rates and a number of complaints related to service, facility completeness, and the guests' stay experience. To ensure the sustainability of service quality in this situation, research is needed on the components that influence guest satisfaction. The objective of this research is to study how service quality, service perspective, and customer experience affect the satisfaction of guests staying at The Manggar Guesthouse. A quantitative method was used by conducting a survey of 112 participants selected through a purposive sampling method. The research data was collected through a four-point Likert scale questionnaire, complemented by documentation and observation as supporting data. The research instruments underwent validity and reliability testing, and the data was analyzed using classical assumption tests and multiple linear regression. The research results indicate that service quality (t = 2.828; p = 0.006), customer experience (t = 3.354; p = 0.001), and service perspective (t = 4.835; p = 0.000) partially and significantly influence guest satisfaction. Simultaneously, the three variables also have a significant effect, with an F count of 40.300 and p = 0.000. The adjusted R2 value of 0.515 indicates the contribution of the three variables to guest satisfaction. Thus, these three factors should be the main focus in the strategy for improving the quality of accommodation management.